4n + 3 = 15 4n +3 - 3 = 15 - 3 4n = 12 4n/4 = 12/4 n = 3
It is 4n-13 and so the next number will be 11
The nth term in this sequence is 4n + 3.
To find the equation of a sequence, you first have to look at the differences between the numbers. In this case the differences are 4, and 4. Thus the equation begins 4n. The sequence minus 4n is: 3, 3, 3 Thus the equation in its entirety is that the value of the term in position n is 4n+3
Un = 4n - 9
4n + 3 = 15 4n +3 - 3 = 15 - 3 4n = 12 4n/4 = 12/4 n = 3
1
3 + 3n = 9 + 2n + 4n n = -2
n3 + 3n2 + 4n + 12 = (n3 + 3n2) + (4n + 12) = n2(n + 3) + 4(n + 3) = (n2 + 4)(n + 3).
N=3.
4n+13=1 -13 -134n=-12/4 /4n=-3
4n + 3 = 31n 3 = 27n n = 3/27
To solve for n in the equation 4n + 3 = 19, you first need to isolate the variable n. Start by subtracting 3 from both sides of the equation to get 4n = 16. Then, divide both sides by 4 to find n = 4. Therefore, the solution to the equation is n = 4.
4n + 9 = -3 Now, we take away 9 from both sides 4n = -12 Now divide by 4 n = -3
-2n
Yes. Multiplying out the brackets on the second one: 4(n + 3) = 4×n + 4×3 = 4n + 12.
7n + 2 = 4n + 17Subtract 2 from each side:7n = 4n + 15Subtract 4n from each side:3n = 15Divide each side by 3:n = 5